2014
DOI: 10.1007/s11099-014-0059-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of elevated CO<sub>2</sub> on growth, physiology, yield, and quality of tomato (Lycopersicon esculentum Mill) cv. Arka Ashish

Abstract: Tomato meets the dietary nutrient and antioxidant requirements of diverse populations. Being a C 3 crop and an important vegetable, it is likely to be influenced by increased CO 2 concentrations under climate change situation. This study was conducted to investigate the effects of elevated CO 2 on overall physiology, water relations, growth, yield, and fruit quality of tomato (Lycopersicon esculentum Mill) cv. Arka Ashish. Plants were grown at elevated CO 2 [550 (EC 550 ) and 700 (EC 700 ) ppm of CO 2 ] in ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 53 publications
4
42
1
Order By: Relevance
“…Furthermore, it can reduce water consumption, thereby increasing dry matter production and yield via increased plant‐level water use efficiency (WUE plant ; Kaminski et al , Pazzagli et al , da Silva et al ). Moreover, elevated CO 2 also increases Pn while decreasing Tr, therefore increasing leaf‐level water use efficiency (WUE leaf ; Mamatha et al , Li et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it can reduce water consumption, thereby increasing dry matter production and yield via increased plant‐level water use efficiency (WUE plant ; Kaminski et al , Pazzagli et al , da Silva et al ). Moreover, elevated CO 2 also increases Pn while decreasing Tr, therefore increasing leaf‐level water use efficiency (WUE leaf ; Mamatha et al , Li et al ).…”
Section: Introductionmentioning
confidence: 99%
“…These results agreed with those of a previous study. Mamatha et al [9] found that the total chlorophyll content was higher when plants were grown with 380 and 550 ppm CO2 than with 700 ppm CO2. In photosynthesis, chlorophyll is a vital component in the lightharvesting complex (LHC), which absorbs and transports photons to the reaction center of photosystems [57].…”
Section: Chlorophyll Content Quantum Yield and Stomatal Conductancementioning
confidence: 99%
“…Under high CO 2 , a decrease in stomatal opening and reduction in stomatal conductance occurred in order to balance the rate of absorbing CO 2 and photosynthesis. Although the stomatal conductance decreased with elevated CO 2 , the photosynthesis increased with CO 2 enrichment [9,13,69]. The different characteristics of stomatal conductance between A. membranaceus and C. lanceolata may be because different species respond differently to the CO 2 concentration.…”
Section: Chlorophyll Content Quantum Yield and Stomatal Conductancementioning
confidence: 99%
See 1 more Smart Citation
“…The e[CO 2 ] also induced necrosis and chlorosis of leaves. In addition, plants show some morphological and physiological changes under e[CO 2 ] concentration (Mamatha et al, 2014). Under e[CO 2 ], a steep CO 2 concentration gradient was observed between the outside and inside of the leaf, allowing great amounts of CO 2 to diffuse into the leaf (Singh and Agrawal, 2015).…”
Section: Introductionmentioning
confidence: 99%